Biomass and Methane Production in Double Cereal Cropping Systems with Different Winter Cereal and Maize Plant Densities - Massimo Blandino; Mattia Scapino; Luca Rollè; Elio Dinuccio; Amedeo Reyneri (Agronomy, 2023)
The biogas supply chain requires a correct combination of crops to maximize the methane yield per hectare. Field trials were carried out in North Italy over three growing seasons, according to a factorial combination of four cropping systems (maize as a sole-crop or after hybrid barley, triticale and wheat) and two maize plant densities (standard, 7.5 plants m−2 and high, 10 plants m−2) with the plants harvested as whole-crop silage. The specific methane production per ton was measured through the biochemical methane potential (BMP) method, while the methane yield per hectare was calculated on the basis of the BMP results and considering the biomass yield. The average methane yield of wheat resulted to be equal to 4550 Nm3 ha−1, and +17% and +28% higher than triticale and barley, respectively, according to the biomass yield. A delay in maize sowing reduced the yield potential of this crop; the biomass of maize grown after barley, triticale and wheat was 20%, 33% and 47% lower, respectively, than maize cultivated as a single crop. The high plant population increased the biomass yield in the sole-crop maize (+23%) and in the maize grown after barley (+20%), compared to the standard density. The highest biomass (32 t ha−1 DM) and methane yield (9971 Nm3 ha−1) within the cropping systems were obtained for barley followed by maize at a high plant density. This cropping system increased the methane yield by 46% and 18%, respectively, compared to the sole-crop maize or maize after triticale at a standard density. The smaller amount of available solar radiation, resulting from the later sowing of maize, reduced the advantage related to the application of a high plant density.